Randomised clinical study: GR‐MD‐02, a galectin‐3 inhibitor, vs. placebo in patients having non‐alcoholic steatohepatitis with advanced fibrosis. Issue 11 (24th October 2016) - Harrison, S. A.; Marri, S. R.; Chalasani, N.; Kohli, R.; Aronstein, W.; Thompson, G. A.; Irish, W.; Miles, M. V.; Xanthakos, S. A.; Lawitz, E.; Noureddin, M.; Schiano, T. D.; et al.
Summary: Background: Non‐alcoholic steatohepatitis (NASH) and resultant liver fibrosis is a major health problem without approved pharmacotherapy. Pre‐clinical results of GR‐MD‐02, a galectin‐3 inhibitor, suggested potential efficacy in NASH with advanced fibrosis/cirrhosis and prompted initiation of a clinical development programme in NASH with advanced fibrosis. Aim: To evaluate the safety, pharmacokinetics and exploratory pharmacodynamic markers of GR‐MD‐02 in subjects having NASH with bridging fibrosis. Methods: The GT‐020 study was a first‐in‐human, sequential dose‐ranging, placebo controlled, double‐blinded study with the primary objective to assess the safety, tolerability and dose limiting toxicity of GR‐MD‐02, in subjects with biopsy‐proven NASH with advanced fibrosis (Brunt stage 3). The secondary objectives were to characterise first‐dose and multiple‐dose pharmacokinetic profiles and to evaluate changes in potential serum biomarkers and liver stiffness as assessed by FibroScan. Results: GR‐MD‐02 single and three weekly repeated of 2, 4 and 8 mg/kg revealed no meaningful clinical differences in treatment emergent adverse events, vital signs, electrocardiographic findings or laboratory tests. Pharmokinetic parameters showed a dose‐dependent relationship with evidence of drug accumulation following 8 mg/kg (~twofold). Conclusions: GR‐MD‐02 doses were in the upper range of the targeted therapeutic dose determined from pre‐clinical data and were safe and well tolerated with evidence of a pharmacodynamic effect. These results provide support for a Phase 2 development programme in advanced fibrosis due to NASH.